The Influence of Customer Relationship Management and Service Performance on Customer Satisfaction and its Implications for Customer Loyalty of Islamic Banks in Riau - Wali Saputra; Bakri Bakri (Al-Buhuts, 2024)
This study aims to examine the effect of: (1) customer relationship management on customer satisfaction, (2) customer relationship management on customer loyalty, (3) customer satisfaction on customer loyalty, and (4) service performance on customer satisfaction (5) service performance on customer loyalty of Islamic banks in Riau. The research design used in this study is causal quantitative research. The subjects in this study are savings customers in Islamic banks and the objects in this study are service performance, customer relationship management, customer satisfaction, and customer loyalty. The sample in this study amounted to 204 respondents. Data were collected through a questionnaire method, and analysed with a structural equation model. The results showed that: (1) customer relationship management affects customer satisfaction (2) customer relationship management affects customer loyalty, (3) customer satisfaction has no effect on customer loyalty, (4) service performance affects customer satisfaction customer satisfaction, and (5) service performance has no effect on customer loyalty.